DEVELOPMENT AND DESIGN OF A RETRACTABLE STABILIZATION SYSTEM FOR VIDEO CAMERAS ON AN AERIAL PLATFORM - Alexandru Pana (Journal of Industrial Design and Engineering Graphics, 2018)
This article presents a simulation model in Matlab Simulink used to simulate the gimbal movement. The following section shows the gimbal design, implementation of the parameters and model in Matlab Simulink and comparative study between simulations determined data and experimental data.